The Relationship Between Cricket Participation, Health, and Wellbeing: A Systematic Scoping Review - Bullock, Garrett Scott; Perera, Nirmala; Murray, Andrew; Orchard, John; Arden, Nigel A.; Filbay, Stephanie R. (International Journal of Sports Medicine, 2021)
Summarising and synthesising the evidence on cricket health and wellbeing can help inform cricket stakeholders and navigate future research directions. The purpose of this study was to investigate the relationship between cricket participation, health and wellbeing at all ages and playing standards, and identify research gaps in the existing literature. A scoping review was performed from inception to March, 2020. Studies were included if they assessed a construct related to health and/or wellbeing in cricketers, available in English. 219 articles were eligible. Injury incidence per 1,000 player exposures ranged from 1.8–5.7 injuries. 48% of former cricketers experienced persistent joint pain. However, former cricketers reported greater physical activity levels and mental-components of quality of life compared to the general population. Heat injury/illness and skin cancer are concerns and require further research. Cricket participation is associated with an inherent injury risk, which may have negative implications for musculoskeletal health in later life. However, cricket participation is associated with high quality of life which can persist after retirement. Gaps in the literature include prospective studies on health and wellbeing of cricketers, female cricketers, injury prevention strategies, and the impact of cricket participation on metabolic health and lifetime physical activity.
Keywords: injury; workload; osteoarthritis; physical activity; sun exposure; mental health; quality of life